(untitled) (Annals of Medical Research, 2026)
Aim: To determine the prevalence of Morton’s neuroma (MN) among patients referred with a clinical suspicion of MN, identify alternative diagnoses, and assess whether angular measurements and the Vulcan sign may help differentiate. Materials and Methods: This retrospective study included 265 feet from 244 patients (mean age, 50.7±13.0 years; 75% female) referred for magnetic resonance imaging with a presumptive diagnosis of MN between January 2020 and June 2025. All patients underwent radiography and magnetic resonance imaging. Morphometric parameters, including the hallux valgus angle, intermetatarsal angle, and interphalangeal angle (IPA), were measured according to the affected web space (2/3 or 3/4). The Vulcan sign was documented on radiographs. Statistical comparisons were performed using the Mann–Whitney U, chi-square, and Fisher’s exact tests. Results: MN was diagnosed in 167 feet (63.0%), while alternative diagnoses were in 98 (37.0%). Bursitis (32.8%), hallux valgus (30.9%), adventitial bursitis (24.5%), hallux rigidus (12.5%), and stress reaction (8.3%) were the most frequent mimics. The 3/4 IPA was significantly greater in MN than in non-MN feet (p<0.001).ROC analysis confirmed limited discriminatory performance, with the 3/4 IPA achieving an AUC of 0.60. Comparisons between bursitis and non-bursitis groups revealed no significant differences in any angular parameters. The Vulcan sign was significantly associated with MN in both the 2nd (p=0.006) and 3rd (p<0.001) web spaces, but no discriminatory value was found for bursitis. Its diagnostic performance was higher in the third web space (AUC 0.62) than in the second (AUC 0.51). Conclusion: This is the first study conducted exclusively in patients referred with a clinical suspicion of MN. The 3/4 IPA demonstrated a modest yet significant association with MN, while the Vulcan sign showed relative specificity for MN compared with bursitis. These results underscore the importance of detailed assessment in clinical practice to differentiate MN from its mimics.